Effects of pH on rheological characteristics and stability of petroleum coke water slurry - Fu-Yan Gao (KeAi Communications Co., Ltd., 2016)
Abstract In this study, the effects of pH on slurrying properties of petroleum coke water slurry (PCWS) were investigated. The slurrying concentration, rheological characteristics and stability of PCWS were studied with four different types of additives at pH varying from 5 to 11. The results showed that the slurrying concentration, rheological characteristics and stability of PCWS all increased at first and then decreased with increasing pH from 5 to 11, and a pH of around 9 was found to be the most favorable acid–alkali environment to all these three slurrying properties. It was also indicated that only in a moderate alkaline environment can the additives be active enough to react with particle surfaces sufficiently to obtain good slurrying concentration and form a stable three-dimensional network structure, which can support strong pseudoplastic characteristics and good stability. An acid environment was a very unfavorable factor to the slurrying properties of PCWS.